The Effect of Perceived Ease of Use on User’s Intention to Use E- learning with Moodle Application in Higher Education Mediated by Perceived Usefulness - Putra, Iwan Setya; Triatmanto, Boge; Zuhro, Diana (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study aims to examine the effect of perceived ease of use on userâ€™s intention to use mediated by perceived usefulness in the use of e-learning in university. This research is essential because it is important to know the user's desire to use e- learning with the Moodle application in universities, considering that during the Covid-19 pandemic, the Indonesian government determined to apply online learning. There were 200 e-learning users from STIE Kesuma Negara Blitar selected as samples. The data were collected by using questionnaire and were then analyzed by multiple regression analysis and path analysisÂ